Representasi Budaya dan Identitas Digital Influencer di Media Sosial (Studi Etnografi Virtual pada Influencer Hilmi Mokhsen di Media Sosial Instagram) - Maria Milania Fengi; Yermia Djefry Manafe; Yeheskial A. Roen (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines how Hilmi Mokhsen, a digital influencer from Kupang, East Nusa Tenggara, represents culture and constructs his digital identity through his activities on Instagram. The platform is viewed as a cultural arena where identity, social meaning, and performativity are formed and displayed. Hilmi is selected as the subject because he represents a creative young generation that uses social media for self-expression and to present contemporary cultural elements in the digital sphere. The research addresses gaps in previous studies by focusing on the symbolic, cultural, and identity dimensions he constructs through a distinct communication style and strong personal branding. The study explores four key issues: how cultural representation appears in Hilmi’s content; how his digital identity is constructed; how symbolic communication and interaction style shape his engagement with followers; and how audiences respond to the culture and identity he presents. This qualitative research adopts a Virtual Ethnography approach and Cyber Media Analysis across four levels: media space, media documents, media objects, and experience. Grounded in Stuart Hall’s Representation Theory, the study emphasizes representation as an active process of meaning-making through language, images, and cultural symbols. The findings are expected to contribute empirically to Indonesian digital culture studies and offer practical guidance for influencers and the creative industry in developing authentic personal branding.